Happiness Plan - Mallery, Susan (Toronto, Ontario, Canada Mira, 2023)
Three best friends--Heather, who finally sees the beauty of family; Daphne, who is trying to fix her marriage after an emotional affair; and Tori, who has fallen in love with a longtime friend, navigate the joy, and heartache of letting people into their hearts for the very first time.
Heather is happy ... ish. She has a successful business, a cute but contemptuous cat, and best friends Daphne and Tori who know where she's broken and love her anyway. So why does she feel crushed when her ex gets serious about someone new? No problem, she has a plan. More connections will hold her together while her world falls apart, so she finally reaches out to the stranger who might be her dad. Daphne isn't having an emotional affair, despite what her husband believes. He started the rift in their marriage when he said they weren't ready for a baby. They used to be the closest couple she knew. Can they find their way back to one another before it's too late? When Tori forms an inconvenient crush on Daphne's brother-in-law, she suppresses her feelings. Until her apartment floods, and she moves in with the dog-loving doctor. If things go wrong, she could lose her friends. . . but if they go right, she could lose her heart.
Includes a readers guide and recipes.
111986
Keywords: Best friends -- Fiction; Families -- Fiction; Female friendship -- Fiction; Couples -- Fiction; Marriage -- Fiction; Man-woman relationships -- Fiction; Fiction / Friendship; Fiction / Romance / Contemporary; Fiction / Family Life / Marriage & Divorce; Fiction / Family Life / Siblings; Domestic fiction; Romance fiction; Novels